2018
DOI: 10.14419/ijet.v7i3.30.18155
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Brand Loyalty in Telecommunication Industry: a Literatur Review

Abstract: This study focuses on the concept of "brand loyalty". The concept of brand loyalty is an important issue in the telecommunication industry and is one of the strategies in relationship marketing. This paper reevaluates the comprehensive determinants of brand loyalty, by testing the model proposed in previous research as a determinant of brand loyalty. The determinants of brand loyalty are service quality, customer satisfaction and brand trust. Several previous studies have addressed the relationship between ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A study by Ikramuddin et al [39] has identified three determinants that can influence customer loyalty in the telecommunication industry. It is a service-providing industry that has rapidly grown over the past few years due to the use of mobile phones.…”
Section: Ahmed and Moosavimentioning
confidence: 99%
“…A study by Ikramuddin et al [39] has identified three determinants that can influence customer loyalty in the telecommunication industry. It is a service-providing industry that has rapidly grown over the past few years due to the use of mobile phones.…”
Section: Ahmed and Moosavimentioning
confidence: 99%
“…The increasing competitiveness of MSMEs will directly or indirectly affect the performance of MSMEs. according to Ikramuddin, Adam, Sofyan, & Faisal, 2018) increasing customer loyalty to products and brands will improve business performance.…”
Section: Competitiveness Of Smesmentioning
confidence: 99%